Contemporary social research methods - Stark, Rondney. (MicroCase Corporation, 1996)
Contents: Chapter 1. Concepts and Theories; Chapter 2. Steps in the Social scientific process; Chapter 3. Measurement; Chapter 4. Censuses and samples; Chapter 5. Causation and causal Modles; Chapter 6. Basic research designs; Chapter 7. Survey research; Chapter 8. Comparative research: Using aggregate units; Chapter 9: Field research; Chapter 10. Experimental research; Chapter 11. Content analysis and other unobtrusive techniques...